A atuação da Alemanha no fenômeno migratório entre os anos de 2015 e 2016: os refugiados entre o acolhimento e a securitização - Santos, Beatriz Santana Vieira (2021)
The present work deals with the process of securitization of migrants in Germany under the context of the current migratory phenomenon in Europe, occurring, with greater expressiveness, between the years 2015 and 2016. Among the member states of the European Union, Germany has played an important role in welcoming asylum seekers in recent years, being the country in EU that received the most asylum applications in absolute numbers. The objective is to investigate and question the performance of this State in the face of such migratory issue, in order to analyze the main foundations and the effects of the policies adopted in relation to migrants. It is known that, in a second moment of this migratory context, the welcoming measures lost space, given the increase in pressure against the reception of these individuals. In this context, it was possible to verify the implementation of measures for greater control of the entry of migrants and, even, the framing of them as threats to the German State, in its social, cultural, political and economic spheres. The research hypothesis indicates that, despite Angela Merkel's efforts to allow refugees to be accommodated by promoting desecuritization, the authority subsequently indicated security policies, in view of episodes of violence carried out by migrants and due to internal pressures. The methodology suggests the qualitative investigation of documents and speeches about the migratory phenomenon on the agenda and the analysis of policies and measures implemented and defended taking Merkel's role as the main reference. The theoretical-analytical framework implies timely concepts and analyzes offered by the field of International Security, more specifically, by the School of Copenhagen and Paris, since they provide elements for understanding the treatment of the migratory issue in the German security agenda having, as a reference, theoretical and practical aspects of security.